2017
DOI: 10.1016/j.jmbbm.2016.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behaviour of staggered array of mineralised collagen fibrils in protein matrix: Effects of fibril dimensions and failure energy in protein matrix

Abstract: Many biological composite materials such as bone have demonstrated unique mechanical performance, i.e., a combination of superior stiffness and toughness. It has become increasingly clear that the constituents at the nano- and micro-length scales play a critical role in determining the mechanical performance of these biological composites. In this study, the underlying mechanisms governing the mechanical behaviour of the staggered array of mineralised collagen fibrils (MCF) embedded in extra-fibrillar protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Indeed, the cortical bone is a dense connective tissue consisting of dense and hard concentric layers called lamellae [31,57]. Each single lamella consists of mineralized collagen fibrils, a soft and ductile collagen fibrils reinforced with stiff hydroxyapatite crystals [35,40,70]. In each single lamella, the mineralized collagen fibrils, considered as the primary building block of bone [30], are oriented in one direction and rotate relative to the adjacent lamella [73].…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Indeed, the cortical bone is a dense connective tissue consisting of dense and hard concentric layers called lamellae [31,57]. Each single lamella consists of mineralized collagen fibrils, a soft and ductile collagen fibrils reinforced with stiff hydroxyapatite crystals [35,40,70]. In each single lamella, the mineralized collagen fibrils, considered as the primary building block of bone [30], are oriented in one direction and rotate relative to the adjacent lamella [73].…”
Section: Numerical Resultsmentioning
confidence: 99%
“…They found that the mesh size of cohesive elements had a significant effect on the strength of the mineralized fibrils. A recent study 46 investigated the evolution of damage in staggered array of mineralized collagen fibrils (MCF) embedded in extrafibrillar protein matrix modeled by continuum cohesive finite elements. The authors found that the failure mechanisms of the extrafibrillar matrix play a dominant role on the energy dissipation capacity of the system.…”
Section: Discussionmentioning
confidence: 99%
“…Our main assumptions are to neglect the material properties of the interfibrillar matrix and to consider the fibrils linked by cohesive surfaces whose damage process occurs in terms of stiffness degradation. Previously, cohesive behaviors were used for studying the damage mechanisms of bone at different scales. Our approach, on the contrary, is based on cohesive stiffness representative of interfaces with negligible small thicknesses. The main difference between the two approaches is that in surface-based laws the damage evolution describes the degradation of the cohesive stiffness whereas in the continuum-based approach the damage concerns the degradation of the material stiffness.…”
Section: Discussion and Conclusionmentioning
confidence: 99%
“…Thus, CF and its derivatives have incomparable biocompatibility, which has allowed their application in prosthesis, artificial tissue, drug carrier, food and cosmetics [10][11][12]. Furthermore, CF has the features of special microstructure, good mechanical strength, resistance to enzymatic cleavage and unavailability for most microorganisms [10,11,13,14]. Therefore, CF has a great potential application as a biocompatible support material for microbial immobilization.…”
Section: Introductionmentioning
confidence: 99%